1989
DOI: 10.1148/radiology.172.1.2787036
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary histiocytosis X: evaluation with high-resolution CT.

Abstract: Eighteen patients with pulmonary lesions of histiocytosis X were studied with high-resolution computed tomography (CT). Thin-walled cysts were found in all but one patient. The other abnormalities included nodules (n = 14), cavitated nodules (n = 3), thick-walled cysts (n = 7), reticulation (n = 4), ground-glass opacities (n = 4), and irregular interfaces (n = 4). The lesions were most often diffuse (n = 16), with a topographic predominance in the upper or middle lung zones in nine patients. Comparison of CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
15

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(130 citation statements)
references
References 0 publications
1
114
0
15
Order By: Relevance
“…And rarely a few small nodular opacities can be seen (7). Nodules in LCHconsist of several types of inflammatory cells including Langerhans' cells, and the majority of them measure 1 to 5 mmin diameter (5). It is suggested that the presence of these parencymal nodules is helpful to distinguish LCHfrom PLAM (6,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And rarely a few small nodular opacities can be seen (7). Nodules in LCHconsist of several types of inflammatory cells including Langerhans' cells, and the majority of them measure 1 to 5 mmin diameter (5). It is suggested that the presence of these parencymal nodules is helpful to distinguish LCHfrom PLAM (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary Langerhans cell histiocytosis (LCH) is also a rare lung disease characterized by lung infiltrates composed of Langerhans' histiocytes (3), and the radiographic appearance of LCHconsists of cystic lesions and multiple nodular opacities ranging on average from 1 to 5 mm,the largest being 10 mmin diameter (4,5). Both PLAMand LCHhave similar pulmonary cysts, which are defined as air-containing lesions surrounded by thin walls that are not shared, but in general parenchymal large nodules, when present, are helpful in distinguishing LCHfrom PLAM (6).…”
Section: Introductionmentioning
confidence: 99%
“…4 High-resolution CT of the chest is superior to plain films in depicting the nodules and cysts. 5 Nodules are predominant in the early stages of the disease, and cysts-particularly in the costophrenic angles-are a later development. Pneumothorax is reported in 25% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently involves lower lobes [18] Sparing of bases and costo-phrenic angles is typical [19][20][21] Biological character Clonality Invariably reported [22][23][24] Suspect reactive rather than clonal [25] …”
Section: Distribution Of Abnormalitiesmentioning
confidence: 99%
“…Several descriptive studies illustrate the utility of HRCT for delineating the nodules and cysts that often have a characteristic distribution in the upper and mid lung fields (Figure 3) [19,20,76].…”
Section: Radiological Findingsmentioning
confidence: 99%